Brooke's big decision - Jones, Jen (Jones, Jen. Team cheer, 2013)
Now that she is graduating from middle school, Brooke Perrino's parents would like her to attend a private school, but it may mean giving up cheerleading, and her friends are all going to Greenview High School.